2006
DOI: 10.4049/jimmunol.176.4.2448
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for Galα(1,3)Gal Expression in Animals with a Deletion of the α1,3Galactosyltransferase Gene

Abstract: The production of homozygous pigs with a disruption in the GGTA1 gene, which encodes α1,3galactosyltransferase (α1,3GT), represented a critical step toward the clinical reality of xenotransplantation. Unexpectedly, the predicted complete elimination of the immunogenic Galα(1,3)Gal carbohydrate epitope was not observed as Galα(1,3)Gal staining was still present in tissues from GGTA1−/− animals. This shows that, contrary to previous dogma, α1,3GT is not the only enzyme able to synthesize Galα(1,3)Gal. As iGb3 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 56 publications
6
105
0
1
Order By: Relevance
“…We did not detect any amplification of iGb3 synthase, consistent with reports of it being a pseudogene in humans (data not shown and ref. 22). Similar results were obtained by using LPS matured DCs (data not shown).…”
Section: Ifnγ Ng/mlsupporting
confidence: 77%
“…We did not detect any amplification of iGb3 synthase, consistent with reports of it being a pseudogene in humans (data not shown and ref. 22). Similar results were obtained by using LPS matured DCs (data not shown).…”
Section: Ifnγ Ng/mlsupporting
confidence: 77%
“…40). Importantly, while the use of animals deficient in the ␣1,3-galactosyltransferase may appear to be the most attractive option for animal to human xenotransplantation, studies have suggested that some tissues, including the vascular endothelium of deficient animals, may in fact still express minor quantities of Gal␣1-3Gal epitopes (41,42). The most likely explanation for this has been identified as expression of the isogloboside glycolipid (Gal␣1-3Gal␤1-4Glc␤1-Cer) (42), which is controlled by another homologous glycosyltransferase of the CAZy GT6 family, the iGb3 synthase (UDP-Gal:lactosylceramide ␣1,3-galactosyltransferase) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a possibility that iGb3S may also be present in other species and may therefore account for the residual aGal expression in GalT-KO animals. 3 Along these lines, low levels of iGb3S mRNA have been detected both in the GalT-KO mouse and the pig thymus and lung, as well as in pECs. The results of immunization of GalT-KO mice with cells transfected with iGb3S, in comparison to GalT, suggest that aGal synthesized by iGb3S is as immunogenic as GalT.…”
Section: Immunological and Biological Barriers In Xenotransplantationmentioning
confidence: 93%
“…Milland et al 3 Gene inactivation GalT GalT-KO pig Complementarity breeding and SCNT in GalT-KO pig production Nottle et al 4 Gene inactivation GalT GalT-KO pig heart Baboon No improvement in coagulation problems in the GalT-KO context Ezzelarab et al 5 Gene inactivation GalT PBMC from WT vs GalT-KO pig…”
Section: Gnt-i Transfected Pig Cells With Piggnt-i Mutationsmentioning
confidence: 99%
See 1 more Smart Citation